Tuning magnetic behavior of nanoscale cobalt sulfide and its nanocomposite with an engineering thermoplastic - Rumale, Narendra; Arbuj, Sudhir S.; Umarji, Govind; Shinde, Manish; Mulik, Uttam P.; Joy, Pattayil Alias; Amalnerkar, Dinesh P. (Journal of Electronic Materials, 2015)
Nanocomposites containing magnetic nanoparticles embedded in a polymer matrix with good thermal stability (up to 200A degrees C) are technologically important. We report an environmentally benign solid-solid approach for synthesis of cobalt sulfide and its nanocomposite using a thermally stable matrix of polyphenylene sulfide. Physicochemical characterizations reveal the formation of nanoclusters of the hexagonal phase CoS. Even though bulk CoS is nonmagnetic, magnetization studies exhibit anomalous magnetic behavior for phase-pure nanoscale CoS and its nanocomposites.
Keywords: Nanocomposite; polyphenylene sulfide; Solid-solid reaction; superparamagnetic